Engagement in HIV Medical Care and Technology Use among Stimulant-Using and Nonstimulant-Using Men who have Sex with Men. (23rd June 2013) - Horvath, Keith J.; Carrico, Adam W.; Simoni, Jane; Boyer, Edward W.; Amico, K. Rivet; Petroll, Andy E.
Abstract : Aims of this study were to assess the associations between stimulant use and attitudes toward and engagement in HIV medical care and to examine technology use among stimulant-using and nonstimulant-using men who have sex with men (MSM). HIV-positive MSM (n = 276 ; mean age = 42 years; 71% white, non-Hispanic; 43% with college degree) completed an online survey in 2009. Most men (69%) had not missed any scheduled HIV medical appointments in the past year, while 23% had missed at least one, and 9% had not attended any appointments. Stimulant use was significantly associated with not attending any HIV medical appointments in the unadjusted model (relative risk ratio (R R R) = 2.84, 95% CI [1.07, 7.58]), as well as in models adjusted for demographic (R R R = 3.16, 95% CI [1.13, 8.84]) and psychosocial (R R R = 3.44, 95% CI [1.17, 10.15]) factors (P s < 0. 05 ). Fewer stimulant-using than non-stimulant-using men rated HIV medical care a high priority (57% versus 85%; P < 0. 01 ). Few significant differences were found in online social networking or mobile phone use between stimulant-using and non-stimulant-using MSM, even when stratified by engagement in HIV care. Findings indicate that stimulant use is uniquely associated with nonengagement in HIV medical care in this sample, and that it may be possible to reach stimulant-using MSM using online social networking and mobile technologies.